PENGARUH KINERJA SOSIAL DAN KINERJA KEUANGAN PERUSAHAAN DENGAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) SEBAGAI VARIABEL INTERVENING TERHADAP NILAI PERUSAHAAN - Andika Suparjan; Ali Sandy Mulya (Media Riset Akuntansi, Auditing & Informasi, 2012)
Changes in the level of public awareness regarding the development of business in Indonesia, creating a new awareness of the importance of implementing Corporate Social Responsibility (CSR). CSR implies that, every the company has a moral duty to be honest, obey the law, uphold the integrity and incorruptibility. CSR emphasizes that companies should develop ethical business practices and continuous (sustainable) economic, social and environmental. The aim research is to know the effect of social performance (environmental performance and product) and financial performance within CSRdisclosure as an intervening variable towards firm value. The sample used in this study as many as 84 companies from years of research 2005-2009. The analysis techniques used by using path analysis. The results are seen from the R2 value of 84.2% indicates that the performance of social (environmental performance and products) and financial performance of the company have contributed on disclosure of CSR are 84.2% and the rest is influenced by factors that are not included in the model. While the magnitude of the effect on firm value indicated by the R2 value of 53.8% means that the performance of social (environmental performance and products), corporate financial performance, and disclosure of CSR has an influence on enterprise value contribution of 53.8% is influenced by factors that are not included in the model.